Prevalence and Risk Factors of Dance Injury During COVID-19: A Cross-Sectional Study From University Students in China - Dang, Yanan; Koutedakis, Yiannis; Chen, Rouling; Wyon, Matthew A. (Frontiers in Psychology, 2021)
Objectives: Although coronavirus disease 2019 (COVID-19) has transformed the training environment of dancers worldwide, little is known on how this has affected injury prevalence, causes, and risk factors. Methods: An online investigation involving Chinese full-time dance students was conducted (September–November 2020), which covered two 6-month periods just before and during the first COVID-19 lockdown. Results: 2086 students (19 ± 2.4 years) responded to the investigation. Injury prevalence dropped from 39.6% (before the lockdown) to 16.5% (during the lockdown) (p < 0.01). It was noted that a significant increase in injury severity during the lockdown was caused due to a 4.1% increase in moderate-to-severe injuries (p < 0.05). During the lockdown, the injuries on the lower back, feet, and shoulders decreased significantly (p < 0.01), but the knee, ankle, and groin/hip joint injuries remained the same. Fatigue and the recurrence of an old injury remained as the top two perceived causes of an injury between the two periods with the increase in an unsuitable floor (p < 0.01), a cold environment (p < 0.05), and set/props (p < 0.05). The fatigue degree of students decreased (p < 0.01) and their hours of sleep increased (p < 0.01) during the lockdown. Binary Logistic Regression analysis indicated that dance injury is associated with fatigue, the hours of sleep, and the actions taken if they suspect an injury during the lockdown (p < 0.05), but is only related to the time set aside for a cooldown and age before the lockdown period (p < 0.05). Conclusion: Although injury prevalence dropped significantly during the first COVID-19 lockdown in Chinese dance students, the main dance injury characteristics remained the same. Decreased fatigue and longer hours of sleep could explain the aforementioned drop in injury prevalence during the lockdown.